2017
DOI: 10.3144/expresspolymlett.2017.95
|View full text |Cite
|
Sign up to set email alerts
|

Silane grafted natural rubber and its compatibilization effect on silica-reinforced rubber tire compounds

Abstract: Abstract. Natural Rubber (NR) grafted with 3-octanoylthio-1-propyltriethoxysilane (NXT) was prepared by melt mixing using 1,1′-di(tert-butylperoxy)-3,3,5-trimethylcyclohexane as initiator at 140°C with NXT contents of 10 and 20 parts per hundred rubber [phr] and initiator 0.1 phr. The silane grafted on NR molecules was confirmed by Fourier transform infrared (FTIR), proton nuclear magnetic resonance ( 1 H-NMR) and scanning electron microscopy/energy dispersive X-ray spectroscopy (SEM-EDX). Based on 1 H-NMR, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 40 publications
(43 reference statements)
1
18
0
Order By: Relevance
“…The compound viscosity was strongly influenced by the rubber-filler and fillerfiller interactions, also influencing the final properties of the rubber composites. 22 The Mooney viscosity of the compounds slightly increased with the grafting level in NR-g-PHEA, indicating more rubber-filler interactions via hydrogen bonding of the silanol groups on the silica surfaces with hydroxyl as well as carboxyl groups in NR-g-PHEA. In addition, T s2 and T c90 , time to initiate curing and time required for 90% completed curing, tended to decrease with grafting level of NR-g-PHEA from 0 to 10.5%.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…The compound viscosity was strongly influenced by the rubber-filler and fillerfiller interactions, also influencing the final properties of the rubber composites. 22 The Mooney viscosity of the compounds slightly increased with the grafting level in NR-g-PHEA, indicating more rubber-filler interactions via hydrogen bonding of the silanol groups on the silica surfaces with hydroxyl as well as carboxyl groups in NR-g-PHEA. In addition, T s2 and T c90 , time to initiate curing and time required for 90% completed curing, tended to decrease with grafting level of NR-g-PHEA from 0 to 10.5%.…”
Section: Resultsmentioning
confidence: 94%
“…Mooney viscosity and cure characteristics, in terms of scorch time ( t s2 ), optimum cure time ( t c90 ), and delta torque ( M H ‐M L ), extrapolated from cure curves of NR‐g‐PHEA silica‐filled NR composites in Figure are shown in Table . The compound viscosity was strongly influenced by the rubber–filler and filler–filler interactions, also influencing the final properties of the rubber composites . The Mooney viscosity of the compounds slightly increased with the grafting level in NR‐g‐PHEA, indicating more rubber–filler interactions via hydrogen bonding of the silanol groups on the silica surfaces with hydroxyl as well as carboxyl groups in NR‐g‐PHEA.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…9 To balance the processability and reinforcing efficiency of rubber-silica systems, two kinds of enols (propenol and 1-undecylenyl alcohol) and a saturated alcohol (1-undecylic alcohol) were used to modify the surface of silica. Sengloyluan et al 22 reported that a silane-grafted NR in the compound improved the filler-rubber interactions and significantly increased the tensile properties of the silica-filled NR compounds. 11 In addition, many other experimental efforts have also been made to investigate the influence of silane coupling agents on silica-filled rubber.…”
Section: Introductionmentioning
confidence: 99%